Digital-Based Knowledge Management Model in Improving Performance and Competitiveness Insurance Brokerage Companies in the Era of Financial Industry Transformation - Budirachman, Ardhyanto (Green Publisher Indonesia, 2025)
The insurance brokerage industry in Indonesia faces digital disruption, regulatory shifts, and fragmented knowledge systems, necessitating integrated digital KM for strategic transformation. Despite existing studies on KM in financial services, sector-specific models for brokerages remain scarce. This research aims to (1) examine how digital KM drives strategic transformation, (2) assess the roles of digital HR, IT infrastructure, cyber risk, and regulatory adaptation, and (3) develop a validated model for brokerage firms. A deductive quantitative approach using PLS-SEM analyzed data from 300–500 Indonesian brokerage managers via structured questionnaires. The model tested hypotheses on five enablers’ influence on KM-mediated transformation. Digital KM significantly enhances transformation (β = 0.316, p < 0.001), with IT infrastructure (β = 0.301) and digital HR (β = 0.274) as primary drivers. Cyber risk (β = 0.193) and regulatory adaptation (β = 0.210) also contributed, albeit with smaller effects. The model explained 59.4% of transformation variance (R² = 0.594), demonstrating strong predictive power (Q² > 0.35). Organizations must embed KM into core processes and leadership strategies, while industry collaboration and policymakers should standardize KM governance. Future research should explore longitudinal impacts and AI-enhanced KM systems.